Web-based Savings and Payment Management Application with Payment Gateway Integration (Case Study of MI Islamiyah Pengatigan Rogojampi) - Moh. Aqil Mukhtar Alfarera; Adi Susanto; Firman Santoso (Universitas Islam Raden Rahmat, Malang, 2025)
The development of information technology encourages schools to improve the efficiency of administrative services, including in the management of student savings. At MI Islamiyah Pengatigan Rogojampi, recording savings is still done conventionally using a savings book, which risks causing recording errors, damage, and data loss. This research aims to design and develop a website-based student savings information system and mobile application, so that the process of recording and managing savings can be done more efficiently, accurately, and transparently. The system development uses the Research and Development (R&D) method with the System Development Life Cycle (SDLC) approach of the Waterfall model which includes the stages of analysis, design, implementation, testing, and maintenance. The system is also integrated with Mitrands Payment Gateway to support online deposit and withdrawal transactions. The test results show that the system runs according to user needs, increasing the speed of recording up to 50% more efficiently and reducing the recording error rate by 90%. In addition, 95% of users expressed satisfaction with the ease of access to balance information and savings history. In conclusion, this system has succeeded in increasing the effectiveness, accuracy, and transparency of student savings management and encouraging early understanding of financial literacy.